Sounds of Home: A Survey of Local Music Collection Management Practices in Canadian Libraries - Doi, Carolyn; Luyk, Sean (CAML Review / Revue de l’ACBM, 2019)
This paper describes the findings of a national survey of local music collection managers in Canadian libraries in 2018. The survey aims to capture a snapshot of local music collection management practices by identifying areas where collection managers make use of specialized skills and competencies and where practices may be improved. An online questionnaire was sent to local music collection managers in Canadian libraries and consisted of 20 questions that addressed demographics, collection scope, collection development, promotion, access, and preservation. The results show that local music collections are diverse in scope and include a wide range of formats. Many include archival materials or are described or organized using archival principles. Collection managers use a range of strategies to build and develop local music collections, including working with community members and donors to identify, select, and purchase collection materials. Collections are used most frequently by community members and researchers to conduct scholarly or historical research. Outreach and promotion are areas where collection managers are using diverse strategies, including community engagement, event hosting, and online marketing, to build awareness of collections. Physical and digital preservation practices are being implemented by most participants, and online access to collections is often available through additional collection description or digitization. Collection managers may face challenges due to the unique nature of local music collections. Strategies for collection management, collection development, outreach, or promotion may fall outside traditional professional skill sets or competencies. Areas for development include donor relations, community engagement, and archival collection management.